Synchrotron FTIR characterisation of automotive primer surfacer paint coatings for forensic purposes - Maric, Mark; Van Bronswijk, Wilhelm; Lewis, Simon; Pitts, K. (Elsevier, 2014)
Synchrotron FTIR microspectroscopy was used to characterise and assess the chemical diversity of electrocoat primer, primer surfacer and basecoats of automotive paint samples from 75 vehicles representing a range of international car manufacturers. Significant diversity was found in the synchrotron FTIR data from the primer surfacer coats. Classification using principal component analysis revealed 14 discrete groups, which could be associated with the country of manufacture, the specific manufacturer and manufacturing plant, the year of manufacture of the vehicle and in some instances the number of layers in the paint system. The model generated from the primer surfacer was significantly more discriminating than a previous model generated from FTIR analysis of clear coats of the same vehicles. Analysis of the primer surfacer also avoids issues of possible environmental degradation and component migration seen with FTIR analysis of automotive clear coats. Providing such information concerning vehicle origin would aid in the development of investigative leads from the analysis of questioned automotive paint samples located at the scene of a crime or on the body/clothing of a hit and run victim.